Factors influencing business intelligence and analytics usage extent in South African organisations - P. Lautenbach; K. Johnston; T. Adeniran-Ogundipe (South African Journal of Business Management, 2017)
Through extensive use of business intelligence and analytics, organisations are better positioned to support fact-based decision making, ultimately leading to improved organisational performance. However, while some organisations recognise and exploit the benefits of business intelligence and analytics use, others fail to capitalise on its potential. It is pertinent therefore to examine factors influencing Business Intelligence and Analytics use within organisations. The three contexts of the Technology-Organisation-Environment (TOE) framework was used as the foundational framework. It is hoped that the findings presented will contribute to a greater understanding of factors influencing business intelligence and analytics usage extent to researchers and practitioners alike. Organisations seeking to promote fact-based decision making through greater business intelligence and analytics use will apply and be better equipped to drive such endeavours.
Keywords: 650